PENGARUH STRUKTUR ASET DAN STRUKTUR MODAL TERHADAP CASH FLOW SHOCK - Dewi Kusuma Wardani; Hilda Vivi Christiyanti (AKUNTANSI DEWANTARA, 2018)
The purpose of this study is to determine the effect of asset structure and capital structure on cash flow shock. This research is classified as causality research. The population of this research is all manufacturing companies listed on the Indonesian Stock Exchange. The sampleS used in this study are 10 companies with five years research period from 2012-2016, so that the sample of research used as many as 50 samples. Data collection methods in this study using purposive sampling. Data analysis technique used is multiple linier regression. The classical assumption test used in this research are normality test, multicollinerarity test, heteroscedasticity test, and autocorrelation test. The result of this study shows the significance of the asset structure is 0,818 and the capital structure is 0,038. Thus can be interpreted asset structure has no effect on cash flow shock. In contrast, capital structure has a positive effect on the cash flow shockKeywords: Asset Structure, Capital Structure, Cash Flow Shock.